Identification of Rana dybowskii Ferritin-Heavy chain gene and analysis of its role during bacterial infection - Huimin Ren; Ye Liu; Yutong Liu; Yiming Liu; Hina Hassan; Yufen Liu; Peng Liu; Wenge Zhao (PLoS ONE, 2025)
Ferritin is widely present in organisms, which can maintain iron relatively stable and participate in the immune response. In this study, the full-length coding sequence (CDS) of the Rana dybowskii ( R. dybowskii ) Ferritin-Heavy Chain ( Fer-H ) gene was cloned by the polymerase chain reaction (PCR) method and characterized by bioinformatics analysis. In order to further explore its role, the inflammation model was established by using Aeromonas hydrophila ( Ah ). The activity of antioxidant enzymes in some tissues was detected, and the expression level of the R. dybowskii Fer-H ( RdFer-H ) gene was detected by quantitative real-time PCR and Western blot analysis. Bioinformatics analysis revealed that the Fer-H gene was 534 bp long, encoding 177 amino acids, and there was a Pfam Ferritin domain. When compared to other species with the same nucleotide sequence, Rana temporaria has the highest homology (94%) with the Fer-H gene. The activities of antioxidant enzymes indicated that the activities of SOD and CAT increased significantly, while the activity of GSH-Px decreased distinctly. This meant that the bacterial infection had caused serious oxidative damage to R. dybowskii . The qRT-PCR results confirmed the broad expression of the Fer-H gene in all R. dybowskii tissues. Furthermore, the transcription level was significantly up-regulated after bacterial infection, and the protein accumulations were consistent with the transcript levels in liver and muscle tissue according to Western blot after Ah infection. This study hypothesizes that the Fer-H gene contributes to R. dybowskii ’s immune response during bacterial infection. It also broadens the research idea for exploring the anti-infection immune response mechanism of amphibians.